MAKNA STRATEGIS PENGAJARAN BAHASA INGGRIS DI SD - Agus Widyantoro Agus Widyantoro (LPMPP Universitas Negeri Yogyakarta, 1999)
The teaching of English in elementary schools has astrategic and anticipatory significance. The results of theteaching of English at present will affect the quality of theIndonesian human resources early in the coming 21 * century.Because at that time Indonesia will enter the free marketera, improvements on the quality of the human resourcesthrough the teaching of English have to receive enoughattention from all parties involved. In addition, the teachingof English in elementary schools will become the basis forthat at higher levels. Failure in the teaching of English inelementary schools will exert negative effects on the successof such teaching at higher levels.